Understanding the Public Policy of Global Budget Payment Reform Improves the Quality of Public Healthcare From the Perspective of Patients in China - Li, Lele; Zhang, Shuo (Frontiers in Psychology, 2022)
The transformation from retrospective to prospective payment system is significant to improve the quality of public healthcare (QPH). This article used the quasi-natural experiment of the global budget payment reform of government (GBR) in Chengdu, adopted the DID method to estimate the effect of the GBR on the QPH and concluded that GBR has a significant positive impact on the healthcare outcome and has a significant effect on improving QPH. Policy implications drawn from the results show that government should continue to explore compound healthcare insurance payment method (HPM), improve the governance capabilities of government, reduce transaction costs, improve healthcare insurance reimbursement policies, adjust the proportion of healthcare insurance reimbursements, continuously optimize the allocation of healthcare resources, establish an incentive mechanism to improve the QPH and realize the pareto optimal choice of healthcare resource allocation.